Association between pioglitazone use and head and neck cancer: Population‐based case‐control study. Issue 4 (13th December 2019) - Yang, Tzong‐Hann; Xirasagar, Sudha; Cheng, Yen‐Fu; Wu, Chuan‐Song; Kao, Yi‐Wei; Shia, Ben‐Chang; Lin, Herng‐Ching
Abstract: Background: This study aimed to evaluate the association between pioglitazone use and the occurrence of head and neck cancer. Methods: Data for this case‐control study were retrieved from the Taiwan National Health Insurance Research Database. A total of 21 464 diabetic patients newly diagnosed with head and neck cancers were identified. We used propensity score matching to select 64 392 comparison patients (3:1 ratio). Multiple logistic regression modeling was used to examine the association of head and neck cancer with pioglitazone use in the 5 years preceding the cancer diagnosis. Results: Bivariate analysis showed a significant difference in the prevalence of prior using pioglitazone between cases and controls (19.3% vs 18.5%, P  < .001) was observed. Multiple regression analysis showed adjusted odds of pioglitazone use of 1.06 (95% CI: 1.02‐1.10) among cases relative to controls. Conclusions: Prior pioglitazone use was associated with oral cavity cancer.